PENGARUH KECERDASAN EMOSIONAL PEMIMPIN, MOTIVASI KERJA DAN SOFTSKILL TERHADAP KINERJA PEGAWAI CABANG DINAS PENDIDIKAN WILAYAH PROVINSI SUMATERA BARAT (Studi Kasus Kepala SMA, SMK Dan SLB) - Isra Jusweldi; Evi Susanti Tasri; Dona Amelia (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to determine and analyze the influence of the leader's emotional intelligence, work motivation and soft skills on the performance of the Regional I Branch of West Sumatra Province employees. The number of respondents who were involved in this study were 92 respondents , all respondents were Heads of SMA, SMK and SLB Branch Office Region I West Sumatra Province. This type of research is quantitative research with SEM ( Structural Equation Modeling) analysis technique. Data was collected using a questionnaire and analyzed using the PLS SEM program . The results of this study show 1) leader's emotional intelligence has a positive and significant effect on the performance of Regional I Branch Office employees at P-value 0.001 2) work motivation has a positive and significant effect on employee performance at P- value 0.00 6 . Meanwhile , soft skills have no significant effect on the performance of the Regional I Branch Office employees of West Sumatra Province . Based on the results of PLS SEM analysis showed that the relationship given emotional intelligence and motivation leader by 67 , 2 %, while the remaining 32 , 7 % is influenced by other variables outside of this research model.